2011
DOI: 10.4049/jimmunol.1002057
|View full text |Cite
|
Sign up to set email alerts
|

Individual Genetic Variations Directly Effect Polarization of Cytokine Responses to Superantigens Associated with Streptococcal Sepsis: Implications for Customized Patient Care

Abstract: Host immunogenetic variations strongly influence the severity of group A streptococcus sepsis by modulating responses to streptococcal superantigens (Strep-SAgs). Although HLA-II–DR15/DQ6 alleles strongly protect against severe sepsis, HLA-II–DR14/DR7/DQ5 alleles significantly increase the risk for toxic shock syndrome. We found that, regardless of individual variations in TCR-Vβ repertoires, the presentation of Strep-SAgs by the protective HLA-II–DR15/DQ6 alleles significantly attenuated proliferative respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
(67 reference statements)
1
21
1
Order By: Relevance
“…In contrast, individuals with the 'protective' HLA-II-DR15/DQ6 haplotype have a lower risk of severe sepsis. 18 These observations in humans are supported by studies which show that transgenic mice expressing only the protective HLA-II DQ6 allele are also protected from severe sepsis when infected with Group A Streptococcus. 19 Whether either of these HLA-II alleles exert a direct influence on cytokine production (via their presentation of Stretococcal superantigen to antigen presenting cells), or is in linkage disequilibrium with other pro-inflammatory gene polymorphisms in the MHC, remains unknown.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, individuals with the 'protective' HLA-II-DR15/DQ6 haplotype have a lower risk of severe sepsis. 18 These observations in humans are supported by studies which show that transgenic mice expressing only the protective HLA-II DQ6 allele are also protected from severe sepsis when infected with Group A Streptococcus. 19 Whether either of these HLA-II alleles exert a direct influence on cytokine production (via their presentation of Stretococcal superantigen to antigen presenting cells), or is in linkage disequilibrium with other pro-inflammatory gene polymorphisms in the MHC, remains unknown.…”
supporting
confidence: 67%
“…8 But the extent of the human cellular and cytokine immune response to microbial challenge is genetically determined, varies considerably between one patient and another, and is independent of the virulence of the infecting bacterial strain. [9][10][11] Individuals whose genome contains fewer pro-inflammatory genetic polymorphisms mount an abrogated response to microbiological challenge, with associations between proinflammatory gene polymorphisms and clinical outcomes recorded for a wide variety of infections, including streptococcal septic shock, 11-15 community acquired pneumonia, 16 and meningococcal meningitis 17 ( Table 1).…”
Section: Eyementioning
confidence: 99%
“…Inability to contain these responses results in severe sepsis, substantial morbidity, and, in many cases, death. Additional studies of humanized HLA class II transgenic mice enabled us to corroborate the role of SAgs in severe invasive GAS infections and revealed that genetic variations in host HLA class II molecules that present SAgs to T cells expressing variable TCR V␤ elements differentially potentiate severity, manifestations, and outcomes of GAS sepsis (24,25).…”
mentioning
confidence: 96%
“…Inability to contain these responses results in severe sepsis, substantial morbidity, and, in many cases, death. Additional studies of humanized HLA class II transgenic mice enabled us to corroborate the role of SAgs in severe invasive GAS infections and revealed that genetic variations in host HLA class II molecules that present SAgs to T cells expressing variable TCR V␤ elements differentially potentiate severity, manifestations, and outcomes of GAS sepsis (24,25).Ensuing studies using distinct, conventional, inbred mouse strains corroborated the contributions of variations in host genetic factors in manipulating the severity and outcomes of GAS sepsis (26-28). However, because of the restricted genetic variations in traditional inbred mouse strains, we used genetically diverse panels of recombinant inbred BXD mouse strains whose genetic variations resemble those seen in humans and that will …”
mentioning
confidence: 98%
“…The various manifestations of GAS infections are mediated by several modes of pathogenic adaptation, where bacteria that are adapted to evade host immune defenses are enriched for, and these successfully colonize and survive in the host and are transmitted to infect another host. We have shown that host factors and host-pathogen interactions also play a pivotal role in modulating and potentiating the severity and manifestations of invasive GAS infections (12,(14)(15)(16)(17).…”
mentioning
confidence: 99%